Policing for Conflict Zones: What Have Local Policing Groups Taught Us?. Issue 1 (3rd August 2017) - Baker, Bruce
The police are invariably severely reduced or even cease to be active in times of conflict. Policing as an activity, however, persists, with local groups taking up the role of maintaining order and combating crime. Such local policing is very diverse in its practices and in the nature of its links with the state. Using examples of local policing practices in four sub-Saharan conflicts, this article considers different patterns of harnessing local capacity to provide policing services. The patterns range from authorities utilising existing local policing providers or initiating new local responses, to local non-government organisations [NGOs] seeking to fill policing gaps left by the state, or long-established local provision continuing unchanged. Each response, whether one of cooperation, delegation, neglect or abandonment, is evaluated for its effectiveness, and lessons to be learned from their practices are offered. Together the four case studies suggest new pathways to achieving police effectiveness and reform in challenging conflict environments.